(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2026)
Graphical representations are used to present information on a wide variety of subjects. Such elements can be explored in different ways, including their use connected to the social context of children. The use of Digital Educational Resources (DER) is justified by their digital nature, which can enhance teaching and learning processes as well as content comprehension. This research aimed to analyze the contribution of the DER “Turma da Mila em: Construindo Gráficos” to the development of reading comprehension focused on graph interpretation. It is a qualitative study, descriptive and exploratory in nature, whose data collection was based on the analysis of the DER and its interdisciplinary potential. The observations were carried out during a geography class that addressed the theme of children’s games, within the context of the literacy cycle, involving 18 first-grade elementary school students. Regarding the analysis of the DER, it was observed that the activities promote reflections on the structure of an investigation, since the user needs to understand the references used in the construction of the graph. Its use contributed to the engagement and understanding of how to construct simple graphs, fostering reflections on data, samples, and data collection instruments.